Guideline to a happy marriage: an instrumental case study on the perspectives of persons with visual disability - Teoh, Jia Long; Muhammad Idris Bullare @ Bahari (Unit Penyelidikan Psikologi dan Kesihatan Sosial UMS, 2019)
The purpose of this investigation is to understand the strategies involved to improve or maintain marital happiness among married persons with visual disability. This study has adopted the instrumental case study design (Stake, 1995). A total of 10 married persons with visual disability with varying conditions have participated in this investigation. This study has utilized the qualitative content analysis as a method of data analysis. A total of five themes related to the strategies to improve or maintain marital happiness of married persons with visual disabilities have been constructed namely: 1) assisting the partner, 2) establishing healthy interaction, 3) being modest, 4) seeking divine intervention, and 5) avoid comparison. This study will enable visually disabled persons, families, and the society to understand how to improve or maintain happiness in marriage. Persons with disabilities would like to be independent, to contribute to society, as well as having the same desires as the non-disabled thus, eliminate the stigma towards persons with disabilities.